2004
DOI: 10.1002/bjs.4603
|View full text |Cite
|
Sign up to set email alerts
|

Late follow-up of a randomized trial of surgery plus tamoxifen versus tamoxifen alone in women aged over 70 years with operable breast cancer

Abstract: Omission of primary surgery in unselected elderly women with operable breast cancer who were fit for the procedure resulted in an increased rate of progression, therapeutic intervention and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
99
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(104 citation statements)
references
References 19 publications
3
99
0
2
Order By: Relevance
“…None of the studies evaluated the oestrogen receptor status of the women they recruited. Four eligible trials addressing surgery plus endocrine therapy vs primary endocrine therapy were identified, of which three have reported outcome data (Willsher et al, 1997;Capasso et al, 2000;Mustacchi et al, 2003;Fennessey et al, 2004), although there is currently no data from one in a form that can be meta-analysed (Capasso et al, 2000). Not all trials identified provided adequate information on all outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…None of the studies evaluated the oestrogen receptor status of the women they recruited. Four eligible trials addressing surgery plus endocrine therapy vs primary endocrine therapy were identified, of which three have reported outcome data (Willsher et al, 1997;Capasso et al, 2000;Mustacchi et al, 2003;Fennessey et al, 2004), although there is currently no data from one in a form that can be meta-analysed (Capasso et al, 2000). Not all trials identified provided adequate information on all outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of three trials was graded as A (Fentiman et al, 2003;Mustacchi et al, 2003;Fennessey et al, 2004) with the rest being graded as B (Gazet et al, 1994;Willsher et al, 1997;Kenny et al, 1998;Capasso et al, 2000). No potentially eligible study was excluded from the review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations